2010
DOI: 10.1016/j.jvs.2010.02.012
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of drug modulation of abdominal aortic aneurysm growth through 25 years of surveillance

Abstract: Diabetes or its medications, or both, have a negative effect on AAA growth. Because of polypharmacy, demonstrating the independent effects of individual drugs affecting the renin-angiotensin system was not possible. In light of this analysis, however, strong associations between angiotensin-receptor blockers and aldosterone-receptor blockers and slowed AAA progression are credible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(112 citation statements)
references
References 22 publications
4
105
1
2
Order By: Relevance
“…The Chichester small AAA surveillance study suggested an association between ARB prescription and reduced AAA progression. 71 However, in contrast, a report from the UK Small Aneurysm Study group reported a small but significant association between ACE-I prescription and increased AAA expansion. 72 This significant difference remained after adjustment for known confounders such as smoking, diabetes, BP and peripheral atherosclerosis.…”
Section: Angiotensin-converting Enzyme Inhibitionmentioning
confidence: 94%
“…The Chichester small AAA surveillance study suggested an association between ARB prescription and reduced AAA progression. 71 However, in contrast, a report from the UK Small Aneurysm Study group reported a small but significant association between ACE-I prescription and increased AAA expansion. 72 This significant difference remained after adjustment for known confounders such as smoking, diabetes, BP and peripheral atherosclerosis.…”
Section: Angiotensin-converting Enzyme Inhibitionmentioning
confidence: 94%
“…A previous ultrasound surveillance study involving 1269 patients with abdominal aortic aneurysm found that the prescription of potassium sparing diuretics (presumed to be mainly the MR antagonist spironolactone) was associated with a reduced rate of aneurysm expansion, although this association was lost after adjusting for other medications. 10 Hyperaldosteronism has also been associated with cerebral aneurysm formation in patients. 11 Based on the above data it is tempting to conclude that aldosterone is the primary effector of angiotensin II in stimulating aortic aneurysm and dissection in mice models and thus a possible target for drug therapy.…”
Section: See Accompanying Article On Page 1568mentioning
confidence: 99%
“…A previous ultrasound surveillance study involving 1269 patients with abdominal aortic aneurysm found that the prescription of potassium sparing diuretics (presumed to be mainly the MR antagonist spironolactone) was associated with a reduced rate of aneurysm expansion, although this association was lost after adjusting for other medications. 10 Hyperaldosteronism has also been associated with cerebral aneurysm formation in patients. …”
mentioning
confidence: 99%
“…Interestingly, patients who had stopped ACE I therapy prior to admission were more likely www.intechopen.com to present with ruptured AAA 71 . The effect of ACE I on expansion of AAA is still equivocal, with some studies demonstrating no protective effect of ACE I therapy [72][73] . Thompson et al in a recent observational study of 1269 patients with small AAA who were followed up for a mean of 3.4 years, reported a significant reduction in aneurysm growth rate as a result of ACE inhibitor therapy 72 .…”
Section: Medical Treatment Of Patients With Aaamentioning
confidence: 99%
“…The effect of ACE I on expansion of AAA is still equivocal, with some studies demonstrating no protective effect of ACE I therapy [72][73] . Thompson et al in a recent observational study of 1269 patients with small AAA who were followed up for a mean of 3.4 years, reported a significant reduction in aneurysm growth rate as a result of ACE inhibitor therapy 72 . The follow up data from UK small aneurysm trial does not support the above finding 74 .…”
Section: Medical Treatment Of Patients With Aaamentioning
confidence: 99%